Fundamental fluid dynamic research on configuration of the hand palm in synchronized swimming - Ito, S. (Biomechanics and Medicine in Swimming X, 2006)
In synchronized swimming, the hands usually describe a "figure 8" or an egg-shaped oval during sculling motion. Various types of sculling movements are employed depending upon the actions and purposes, although the function of all sculling motions is to produce lift force through reciprocating motion. Optimal band configurations for sculling are not standardized among athletes and are instead determined empirically by coaches and athletes. In this research, the hydrodynamic characteristics of five band configurations are investigated in a basic study in a steady-state flow field to determine the configuration that produces maximum resultant force.